Reperfusion therapy for ST elevation acute myocardial infarction 2010/2011: current status in 37 ESC countries - Kristensen, Steen D; Laut, Kristina G; Fajadet, Jean; Kaifoszova, Zuzana; Kala, Petr; Di Mario, Carlo; Wijns, William; Clemmensen, Peter; Agladze, Vaja; Antoniades, Loizos; Alhabib, Khalid F; De Boer, Menko-Jan; et al. (European heart journal, 2014)
AIMS: Primary percutaneous coronary intervention (PPCI) is the preferred reperfusion therapy in ST-elevation myocardial infarction (STEMI). We conducted this study to evaluate the contemporary status on the use and type of reperfusion therapy in patients admitted with STEMI in the European Society of Cardiology (ESC) member countries. METHODS AND RESULTS: A cross-sectional descriptive study based on aggregated country-level data on the use of reperfusion therapy in patients admitted with STEMI during 2010 or 2011. Thirty-seven ESC countries were able to provide data from existing national or regional registries. In countries where no such registries exist, data were based on best expert estimates. Data were collected on the use of STEMI reperfusion treatment and mortality, the numbers of cardiologists, and the availability of PPCI facilities in each country. Our survey provides a brief data summary of the degree of variation in reperfusion therapy across Europe. The number of PPCI procedures varied between countries, ranging from 23 to 884 per million inhabitants. Primary percutaneous coronary intervention and thrombolysis were the dominant reperfusion strategy in 33 and 4 countries, respectively. The mean population served by a single PPCI centre with a 24-h service 7 days a week ranged from 31 300 inhabitants per centre to 6 533 000 inhabitants per centre. Twenty-seven of the total 37 countries participated in a former survey from 2007, and major increases in PPCI utilization were observed in 13 of these countries. CONCLUSION: Large variations in reperfusion treatment are still present across Europe. Countries in Eastern and Southern Europe reported that a substantial number of STEMI patients are not receiving any reperfusion therapy. Implementation of the best reperfusion therapy as recommended in the guidelines should be encouraged.
Keywords: STEMI; Hospital Mortality; mužské pohlaví; Workforce; Male; reperfuze myokardu; senioři; Female; Humans; registrace; lidé; Cross-Sectional Studies; Middle Aged; ženské pohlaví; lidé středního věku; Primary percutaneous coronary intervention; Evropa; kardiologie; Percutaneous Coronary Intervention; koronární angioplastika; Myocardial Infarction; Thrombolytic Therapy; koronární jednotky; Europe; trombolytická terapie; dospělí; Registries; Adult; Coronary Care Units; Treatment variation; mortalita v nemocnicích; průřezové studie; pracovní síly; Aged; Cardiology; infarkt myokardu; Myocardial Reperfusion